Method of learning through play to facilitate the activeness of kindergarten students - Wardhani, M Kusuma; Nduru , Masania (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
The activeness of students in the learning process is important because students are the subjects of learning. The teacher as a facilitator has an important role in designing learning to facilitate student activity. However, in reality, kindergarten students were found to be less active in class. This is because the need for its characteristics has not been properly facilitated through the right method. As many as 38% of students did not pay attention to the teacher when explaining, 92% of students did not answer the teacher's questions or in other words, only one student answered the teacher's questions, 15% of students were sleepy and did not follow instructions and 0.7% of students did not complete the assignments given. This study aims to describe a method of learning through play to facilitate the activeness of kindergarten students with a descriptive qualitative research methodology supported by portfolio data that will be used as an instrument in the research, they are in the form of observation for a week, reflection on teaching six times, mentor feedback when teaching authors, and lesson plans. The research population was 13 K-2 grade kindergarten students at a school in Bogor, West Java. It was concluded that this method of learning through play can facilitate student activity because it can attract attention, increase concentration, involve less active students, and develop students holistically.